Targeting P-selectin in acute pancreatitis - Hackert, Thilo; Büchler, Markus W.; Werner, Jens (Expert opinion on therapeutic targets, 2010)
Importance of the field: Acute pancreatitis (AP) is a multifactorial disorder not fully understood yet. In particular, the pathogenetic pathways promoting a severe life-threatening course of AP are the subject of ongoing investigations. P-selectin has been shown to play a central role in the complex pathophysiology in AP as well as various other inflammatory conditions.Areas covered in this review: P-selectin function in AP is reviewed with focus on its dual function as a mediator of leukocyte recruitment and cell adhesion, which implies the unique effect of linking both inflammation and coagulation, especially in the progression from mild to severe necrotizing AP. Potential therapeutic aspects are discussed with regard to the clinical situation.What the reader will gain: A better understanding of the pathogenic role of P-selectin in AP and of the rationale for a therapeutic blockade.Take home message: P-selectin is a glycoprotein that mediates the adhesion of activated platelets and leukocytes to the vessel wall in various inflammatory conditions. Both pathophysiological steps are closely linked and play a key role in the course of severe AP. A treatment approach by inhibition of P-selectin could be of distinct interest as a therapeutic option in severe AP.